2020
DOI: 10.4324/9780429277337
|View full text |Cite
|
Sign up to set email alerts
|

Peer Mentoring in Criminal Justice

Abstract: The background I 1 Introduction: peer mentoring in criminal justice 3 2 The penal voluntary sector, peer mentoring and desistance from crime 12 3 Theorising peer mentoring as a critical relational practice: identity, pedagogy and collective politicisation 38 4 The research field 69 PART TWO Making sense of peer mentoring 89 5 The importance of identity to peer mentoring 91 6 Agency, action and acknowledgement in peer mentoring 117 7 The values and'core conditions'of peer mentoring 141 8 The terror, complexity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 0 publications
1
53
0
Order By: Relevance
“…Within this study, due to the small sample size and limited demographic information, it has not been possible to examine how gender, ethnicity, sexuality, disability or other aspects of diversity figure in mentoring. As highlighted by Buck (2020), mentoring is gendered, and at times can reinforce 'masculine' and 'feminine' stereotypes (e.g. boxing for men and fashion for women), while also providing opportunities to connect via gendered spaces or even challenge gender norms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this study, due to the small sample size and limited demographic information, it has not been possible to examine how gender, ethnicity, sexuality, disability or other aspects of diversity figure in mentoring. As highlighted by Buck (2020), mentoring is gendered, and at times can reinforce 'masculine' and 'feminine' stereotypes (e.g. boxing for men and fashion for women), while also providing opportunities to connect via gendered spaces or even challenge gender norms.…”
Section: Discussionmentioning
confidence: 99%
“…Mentoring has become a popular way of supporting people who have been involved in offending behaviour (Buck, 2020). But how does mentoring help people to change?…”
Section: Introductionmentioning
confidence: 99%
“…The promise of peer mentorship Despite a lack of consistency in the peer-mentorship model, research suggests that peer-focused reentry services appear to be beneficial in a variety of ways (Barrenger et al, 2017;Brown and Ross, 2010;Buck, 2020;Hinde and White, 2019;LeBel, 2007;Matthews et al, 2020;Marlow et al, 2015). First, research suggests that peers in criminal justice settings derive a variety of emotional and psychological benefits, similar to other settings (Buck, 2020).…”
Section: Peer Mentors In Carceral Settingsmentioning
confidence: 99%
“…Despite a lack of consistency in the peer-mentorship model, research suggests that peer-focused reentry services appear to be beneficial in a variety of ways (Barrenger et al, 2017; Brown and Ross, 2010; Buck, 2020; Hinde and White, 2019; LeBel, 2007; Matthews et al, 2020; Marlow et al, 2015). First, research suggests that peers in criminal justice settings derive a variety of emotional and psychological benefits, similar to other settings (Buck, 2020). For instance, Marlow and colleagues (2015) found that peer mentors helped mentees evaluate their choices more effectively and provided guidance about appropriate interpersonal skills and ways of coping, ultimately giving the mentees confidence they could achieve stability.…”
Section: Peer Mentors In Carceral Settingsmentioning
confidence: 99%
See 1 more Smart Citation